Юбилей писателя-фронтовика в тени войны. 100-летие Виктора Астафьева в блогах платформы Dzen.ru - Wawrzyńczak, Aleksander (Slavia Orientalis, 2025)
The article contains a critical review of blogs on the Russian website Dzen.ru, which have focused on the life and work of the outstanding Russian writer Viktor Astafiev. The occasion for the discussion of this topic was the centenary of Astafiev's birth, which fell in 2024. Currently, in Russia, the blogosphere is one of the most important channels of mass communication, having a decisive influence on public opinion. The content presented on these blogs and analyzed in the article shows an ambiguous perception of Astafiev as a soldier of the Great Patriotic War (1941-1945), and as a writer who strongly condemned all wars in his works. The main reason being Russia's current invasion of independent Ukraine. Basically, bloggers whose niche is literature express positive opinions about Astafiev. Nevertheless, pro-Kremlin propagandists and apologists for Soviet totalitarianism have spread ideologically tainted false claims regarding Viktor Astafiev's legacy, aiming to reinforce negative and misleading opinions about the author and his works.